Trends in Character Education for Elementary, Middle and High School Students in Indonesia: Systematic Literature Review - Carsiwan (Indonesian Journal of Educational Research and Review, 2024)
Character education is a multifaceted effort to develop moral and ethical individuals so that they can make a positive contribution to society. The study aims to analyze character education trends among students at the secondary, secondary, and high school levels in Indonesia. The study uses the Systematic Literature Review (SLR) method to investigate character education trends in elementary, primary, and upper secondary school students in Indonesia (systematic literature review). The study is guided by the PRISMA protocol and uses the Covidence platform to facilitate the review process. The sourcing of data was done through the Google Scholar and Crosreef databases with the sources of articles in reputable international journals, using Harzing’s Publish or Perish application. Of the 1,200 articles found, 69 journals were selected to be reviewed through a systematic exclusion and inclusion process. The articles related to auxiliary technology selected in this study were analyzed using quantitative bibliometric studies to map the structure of knowledge. The results of the research show that the trend of character education in Indonesia is experiencing increasing attention and intensive efforts at every level of education. Each level applies a different approach according to the characteristics and needs of student development but still has the same goal, namely, forming a positive personality and good morals. Overall, the study provides a comprehensive overview of the efforts of the character education application in Indonesia, aimed at developing a young generation that not only achieves academically but also has good personalities and morality.